The Influence of Product Reviews and the Credibility of Youtuber Gadgetin on Purchase Intention Among Generation Z in Malang City - Krisensius Umbu Rauta; Emmalia Adriantantri; Sujianto Sujianto (Publikasi Indonesia, 2026)
The rise of gadget reviews on YouTube has established the platform as a key source of pre-purchase information for Generation Z; however, findings on the influence of review quality and YouTuber credibility on purchase intention remain inconsistent. This research gap necessitates further investigation, particularly among Generation Z consumers who actively engage with such content. This study aims to analyze the influence of product reviews and the credibility of YouTuber GadgetIn on purchase intention among Generation Z in Malang City, both partially and simultaneously. This study employs a quantitative explanatory approach, distributing a four-point Likert scale questionnaire online to 122 Generation Z respondents in Malang City who had watched gadget review content on the GadgetIn channel. Data were analyzed using SPSS. The results indicate that product reviews and the credibility of YouTuber GadgetIn simultaneously exert a positive and significant effect on the purchase intention of Generation Z in Malang City, accounting for 42.3% of the variance; the remaining 57.7% is attributable to other factors outside the scope of this study. These findings demonstrate that the quality of clear, informative, and objective reviews as well as YouTuber credibility reflected through expertise and honesty plays a significant role in shaping consumer trust and purchase intention. Accordingly, the findings of this study may serve as a reference for content creators and digital marketers seeking to improve the quality of review presentation and maintain credibility as a strategy for encouraging purchase intention among young consumers.